Zur Vorgeschichte des Ecocriticism bei Gregory Bateson - Frederic Ponten (Recherches Germaniques)
The article examines Gregory Bateson’s contributions to the emergence of Ecocriticism. The starting point of my study is his position paper Style, Grace, and Information in Primitive Art, presented in the Summer of 1967, which deals with the image of a Balinese funerary procession that took place in 1937. In this paper, Bates shows the difficulty of relating the American concept of “cultural pattern”, developed in the 1930s, to an ornamental Balinese art production. This art emerged under colonial conditions in dialogue and exchange with an avant-garde colony of artists and their primitivist notions of original ornamental art. Based on a recontextualization of the image studied by Bateson, I propose an alternative interpretation.